Difficulties in diagnosing antibiotic-associated diarrhea using a clinical case example - V. I. Kryvenko; I. S. Kachan; O. P. Fedorova; A. V. Kechejieva; S. P. Pachomova (Zaporožskij Medicinskij Žurnal)
Aim. To identify challenges in the diagnosis and treatment of a patient with intestinal damage due to long-term use of antibiotics.